Association of bleeding with serotonergic antidepressants in patients receiving left ventricular assist device support. Issue 1 (25th October 2021) - Robinson, Adam C.; January, Spenser E.; Botkin, Kent W.; Vader, Justin M.; Hartupee, Justin C.; Tellor Pennington, Bethany R.
Abstract: Study Objective: This study sought to determine whether SA use is associated with bleeding in patients receiving CF‐LVAD support. Design: A retrospective cohort analysis was conducted of all adult patients who received CF‐LVAD implantation at our institution. Setting: Barnes‐Jewish Hospital between July 1, 2009, and October 1, 2018. Patients: Patients at least 18 years of age who received a HVAD™ (HeartWare Corp.), HeartMate II™ (St. Jude Medical), or HeartMate 3™ (St. Jude Medical) CF‐LVAD and survived for at least 30 days postoperatively were included. Intervention: Patients who received SAs ( n = 203) were compared to those who did not ( n = 391) from 30 days to 18 months following implantation. The primary outcome was the incidence of first bleeding events including gastrointestinal bleed (GIB), epistaxis, or intracerebral hemorrhage (ICH). Measurements and Main Results: During follow‐up, 219 patients had bleeding events: 93 of 203 (45.8%) in the SA group versus 126 of 391 (32.2%) in the control group ( p = 0.001). After adjustment for age, angiotensin‐converting enzyme (ACE) inhibitor and angiotensin receptor blocker (ARB) use, history of bleeding events, history of smoking, and CF‐LVAD type, SA use remained associated with bleeding (adjusted odds ratio: 1.75, 95% confidence interval: 1.22–2.51, p = 0.002). HeartMate 3™ patients experienced less bleeding than HeartMate II™ patients (adjusted odds ratio 0.46, 95% confidence interval: 0.23–0.90, p = 0.024). Conclusions: In this single‐center, retrospective cohort of patients supported with CF‐LVADs, SA use was associated with the incidence of first bleeding events, primarily driven by GIB. Further studies are needed to assess any differential risk of bleeding among SA agents and to assess the utility of altering antithrombotic strategies.